Comparative Study of Ni-Zn LHS and Mg-Al LDH Adsorbents of Navy Blue and Yellow F3G Dye - Idha Yulia Ikhsani; Sri Juari Santosa; Bambang Rusdiarso (Universitas Gadjah Mada, 2016)
Adsorption of disperse dyes from wastewater onto Ni-Zn LHS (layered hydroxide salts) and Mg-Al LDH (layered double hydroxides) has been compared in this study. Effects of initial pH solution, contact time and initial dye concentration were investigated. The ability of the adsorbent to be reused was also studied. The results showed that acidic condition was favorable for the adsorption of each dyes onto both adsorbent. The adsorption kinetics was studied using pseudo-first-order, pseudo-second-order and Santosa’s kinetics models. The experimental data fits well with the pseudo-second order kinetic model. The equilibrium adsorption data were analyzed using Langmuir and Freundlich isotherm models. The results showed that adsorption of navy blue onto both adsorbent followed Freundlich isotherm adsorption, while yellow F3G followed Langmuir isotherm adsorption. In the application for the adsorption the wastewater containing dyes, Ni-Zn LHS has a better adsorption capacity of 52.33 mg/g than that of Mg-Al LDH that 30.54 mg/g. Calcination of the adsorbent which has already been used increased the adsorption capacity of Mg-Al LDH to 84.75 mg/g, but decreased the adsorption capacity of the Ni-Zn LHS to 42.65 mg/g.